Memahami Preferensi Generasi Z dalam Pariwisata Pesisir Halal: Studi Kasus dan Rekomendasi - Putra, Rama Dani Eka; Fitri, Tessa Zulenia; Kurniadi, Deri (Journal of Social and Community Service, 2024)
Understanding the preferences of Generation Z in halal coastal tourism is crucial, given their unique characteristics of prioritizing religious values, sustainability, and authentic experiences. This study aims to provide recommendations for the development of a sustainable tourism industry that positively impacts society and the environment. The methodology employed involves surveys and interviews with Generation Z respondents to identify factors influencing their choices, such as religious aspects, sustainability, and authentic experiences. The findings of this study indicate that Generation Z has unique and specific preferences for halal coastal tourism, reflecting their religious values, sustainability, and desire for authentic experiences.